2018
DOI: 10.1016/j.neuron.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Active Sampling State Dynamically Enhances Olfactory Bulb Odor Representation

Abstract: SummaryThe olfactory bulb (OB) is the first site of synaptic odor information processing, yet a wealth of contextual and learned information has been described in its activity. To investigate the mechanistic basis of contextual modulation, we use whole-cell recordings to measure odor responses across rapid learning episodes in identified mitral/tufted cells (MTCs). Across these learning episodes, diverse response changes occur already during the first sniff cycle. Motivated mice develop active sniffing strateg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 60 publications
11
93
0
Order By: Relevance
“…This increase was invariant of chemical classes and difficulty of the tasks employed ( Figure 5a) and it did not occur in the absence of odor stimuli ( Figure S3). Thus, the time needed to discriminate odors of varying similarity is independent of the sampling behavior and puts our results in unison with the growing consensus that odor coding is sniff frequencyindependent (Jordan et al, 2018a;Shusterman et al, 2018).…”
Section: Sniff-invariant Olfactory Decisionssupporting
confidence: 80%
“…This increase was invariant of chemical classes and difficulty of the tasks employed ( Figure 5a) and it did not occur in the absence of odor stimuli ( Figure S3). Thus, the time needed to discriminate odors of varying similarity is independent of the sampling behavior and puts our results in unison with the growing consensus that odor coding is sniff frequencyindependent (Jordan et al, 2018a;Shusterman et al, 2018).…”
Section: Sniff-invariant Olfactory Decisionssupporting
confidence: 80%
“…How repeated sampling influences olfactory processing by neural circuits in the olfactory bulb (OB) or elsewhere is not well understood. Previous work has shown that rapid sniffing induces adaptation of olfactory sensory inputs to the OB (Verhagen et al, 2007); more recently, we and others have found that inhalation frequency modulates subthreshold membrane potential and spiking patterns in mitral and tufted cells (MTCs; (Bathellier et al, 2008;Carey and Wachowiak, 2011;Díaz-Quesada et al, 2018;Jordan et al, 2018b)). Multiple distinct functions of this frequency-dependent modulation have been proposed, including enhancing olfactory sensitivity, increasing the salience of odorants against a background, and improving fine-scale odor discrimination.…”
Section: Introductionmentioning
confidence: 85%
“…There is also substantial evidence that mitral cells (MCs) and tufted cells (TCs) have distinct odorant response properties and likely contribute differentially to encoding odor information (Nagayama et al, 2004;Griff et al, 2008;Fukunaga et al, 2012; 2018a; Short and Wachowiak, 2019). For example, some studies have reported that MCs appear more subject to inhibition, respond with longer latency relative to inhalation, and may hyperpolarize more frequently than TCs during bouts of high-frequency inhalation (Jordan et al, 2018b). Such differences have led to the suggestion that TCs convey rapid odor "snapshots,"…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual decision making (Romo and Salinas, 2003;Cohen and Newsome, 2004;Gold and Shadlen, 2007;Carandini and Churchland, 2013;Diamond and Arabzadeh, 2013;Svoboda and Li, 2018) is an active process where a movement of the sense organse.g., eyes, ears, nose, fingers or whiskersis crucial to extract task-relevant information (Gibson, 1962;Yarbus, 1967;Youngentob et al, 1987;Jordan et al, 2018). Our understanding of how the brain translates sensory signals into decisions during active sensation has been held back by the experimental difficulty of measuring sensory input to a moving sense organ.…”
Section: Introductionmentioning
confidence: 99%